Atrial Fibrillation in Acute Coronary Syndrome - early onset impact on MACE. (24th May 2021) - Santos, M; Santos, H; Almeida, I; Miranda, H; Sa, C; Chin, J; Almeida, S; Sousa, C; Tavares, J; Santos, L; Almeida, ML
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: on behalf of the Investigators of " Portuguese Registry of ACS " Introduction: Atrial Fibrillation (AF) complicates approximately 10% of acute coronary syndromes (ACS) and it is, therefore, important to access its impact on ACS patients' (pts) prognosis. Objective: To evaluate early onset (≤48h) de novo atrial fibrillation (AF) as predictor of major adverse cardiovascular events (MACE) and in-hospital complications. Methods: Based on a multicenter retrospective study, data collected from admissions between 1/10/2010 and 8/01/2019. Pts were divided in two groups: A – early onset de novo AF (EOAF), and B – late onset de novo AF (LOAF). Patients without data on previous cardiovascular history or uncompleted clinical data were excluded. Univariate logistic regression was performed to assess if LOAF in ACS was a predictor of MACE or complications. Results: 29851 pts had ACS. EOAF occurred in 584 pts (2.0%) and LOAF in 360 pts (1.2%). EOAF were younger (73 ± 13 vs 77 ± 10, p < 0.001) and smokers (21.3% vs 12.1%, p < 0.001). LOAF had higher rates of diabetes mellitus (40.1% vs 30.2%, p < 0.001), angina (30.8% vs 21.4%, p < 0.001), previous ACS (22.5% vs 15.4%, p = 0.006), previous revascularization (percutaneous coronary intervention 14% vs 9.5%, p = 0.032; coronary artery bypass surgery 8.4% vs 3.9%, p = 0.004). ST-segment elevation myocardial infarction (MI) rates were higher in EOAF (56.8% vs 46.9%, p = 0.003) and were admitted directly to the cath lab more often (21.7% vs 13.4%, p = 0.001). Non-ST elevation MI rates were higher in LOAF (44.2% vs 37.7%, p = 0.048). LOAF times from first symptoms to admission were longer (420min vs 183%, p < 0.001), mean brain natriuretic peptide levels were higher (579 vs 447, p = 0.009) and diuretics usage was more frequent (72.8% vs 54.3%, p < 0.001). EOAF had higher rates of heart failure (32.1% vs 17.2%, p < 0.001), atrioventricular block (10.5% vs 7.8%, p = 0.006) and sustained ventricular tachycardia (8.1% vs 3.1%, p = 0.001). LOAF had higher in-hospital mortality (14.2% vs 9.6%, p = 0.031) and longer hospital stay (12 days vs 7 days, p < 0.001). Logistic regression confirmed that EOAF was predictive of in-hospital heart failure (p < 0.001, OR 2.15) and atrioventricular block (p = 0.008, OR 7.46). Regarding 1 year-follow-up, EOAF had poorer prognosis comparing to LOAF (59.3% vs 73.0%, p = 0.018, OR 1.62, CI 1.09-2.42) Conclusion: EOAF is predictive of MACE, namely heart failure and atrioventricular block, and is associated to poorer prognosis comparing to LOAF.